2019
DOI: 10.21873/anticanres.13531
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effectiveness of Orlistat in the Suppression of Human Colorectal Cancer Cell Proliferation

Abstract: Background/Aim: Fatty acid synthase (FASN) provides palmitate for cell membrane formation in colorectal cancer (CRC) cells, however, palmitate is also available in the blood of CRC patients. The aim of this study was to examine whether orlistat, a FASN inhibitor, is able to attenuate CRC cell growth despite the availability of extracellular palmitate. Materials and Methods: Palmitate concentrations were measured in serum from CRC patients and healthy controls. HT-29 CRC cells were treated with orlistat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The anti-proliferative effect of orlistat appears to be associated with FASN inhibition as it was partially reverted by co-treatment of Jurkat cells with SP, the final product of FASN activity. This aspect is of clinical relevance as recently shown by Czumaj et al 46 since SP can be present at high levels in the serum of colon cancer patients, leading to the requirement of higher doses of orlistat for possible therapeutic success. We found also that, beside the inhibition of the enzymatic activity, orlistat is able to reduce FASN protein levels.…”
Section: Discussionmentioning
confidence: 79%
“…The anti-proliferative effect of orlistat appears to be associated with FASN inhibition as it was partially reverted by co-treatment of Jurkat cells with SP, the final product of FASN activity. This aspect is of clinical relevance as recently shown by Czumaj et al 46 since SP can be present at high levels in the serum of colon cancer patients, leading to the requirement of higher doses of orlistat for possible therapeutic success. We found also that, beside the inhibition of the enzymatic activity, orlistat is able to reduce FASN protein levels.…”
Section: Discussionmentioning
confidence: 79%
“…Most authors reported overexpression of lipogenic enzymes in cancer tissues or cells [17]. The overexpression of enzymes from this group, specifically FASN [40] and SCD1 [41] involved in the synthesis of oleic acid, the main component of triglycerides, was also found in CRC. These findings imply that the contents of lipids, including triglycerides, in cancer tissues should be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients received preoperative neoadjuvant treatment and omega-3 FA supplementation. The tissue and serum sample collection was performed as we described previously 3,8 . The tissue samples were collected from both the tumor and normal large intestinal mucosa, at least 5 cm from the tumor interface.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids (FAs) are a heterogeneous group of lipids with different chain length, degree of saturation and metabolic effects 2 . A growing body of evidence shows that CRC is associated with alterations of FA profiles in serum and tumor tissues [3][4][5][6][7][8] . Recently, we demonstrated an increase in the levels of saturated and monounsaturated very long chain FAs in tumor tissues and sera of CRC patients 3 , co-existing with enhanced expression of FA elongases 1 and 6 in cancer tissues 3 .…”
mentioning
confidence: 99%